Involvement of Personnel as a Key Reserve of Raising Efficiency of Today’s Companies’ Work - N. V. Gromova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies a relatively new for Russian economy indicator, i.e. personnel involvement. Practice of development and implementation of personnel involvement programs is rather widely spread in overseas organizations. In Russia programs of raising personnel involvement are used only in big companies. Personnel involvement is considered as an indicator of relations 'organization - worker', when the worker is ready to fulfill functions beyond the frames of his/her job description, to apply extra efforts in order to reach the set goals, to recommend the company as an honest employer and to continue working for the company as long as possible. It was found that personnel involvement is a complicated integrated indicator, which is affected by many factors. The author formulated the key groups of factors determining the level of personnel involvement. By analyzing the practice of home and overseas companies it is shown that employees with high level of involvement can provide higher results of the company work at the same time the interrelation between involvement and key business-coefficients of the company was revealed. Competitive advantages gained by today's companies, which use technologies of raising personnel involvement are grounded. Promising lines and trends of raising personnel involvement are formulated.